2022
DOI: 10.1186/s12916-022-02245-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pyrotinib in advanced lung adenocarcinoma with HER2 mutations: a multicenter, single-arm, phase II trial

Abstract: Background There is currently a lack of effective treatments for non-small cell lung cancer (NSCLC) patients harboring HER2 mutations. We examined the efficacy and safety of, and potential resistance mechanism to, pyrotinib, a pan-HER inhibitor, in advanced NSCLC carrying HER2 mutations. Methods In this multicenter, single-arm, phase II trial, stage IIIB-IV NSCLC patients harboring HER2 mutations, as determined using next-generation sequencing, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“… 20 Clinical trials also have shown that pyrotinib exhibited high efficacy in NSCLC patients harboring activating HER2 mutations. 21 , 22 Therefore, pyrotinib therapy was considered as an option for the late-line treatment in HER2 mutant cancer patients. Large clinical trials should be conducted to verify the treatment efficacy of pyrotinib in HER2 amplified or mutant cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Clinical trials also have shown that pyrotinib exhibited high efficacy in NSCLC patients harboring activating HER2 mutations. 21 , 22 Therefore, pyrotinib therapy was considered as an option for the late-line treatment in HER2 mutant cancer patients. Large clinical trials should be conducted to verify the treatment efficacy of pyrotinib in HER2 amplified or mutant cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Afatinib exposure and brain metastases at baseline had no effect on ORR, PFS, or OS. As the illness progressed, the loss of HER2 mutations and the development of amplification in EGFR and HER2 were discovered [ 106 ].…”
Section: Molecular Targetsmentioning
confidence: 99%
“…Preclinical and phase I clinical data from breast cancer indicate that pyrotinib can irreversibly inhibit multiple HER receptors (EGFR/HER1, HER2, and HER4) and HER2 overexpressing cells in vitro and in vivo. Studies have shown a 19–53% ORR and a median PFS of 5–6 months in pretreated HER2 mutant NSCLC, even in patients that received prior HER2 directed therapy [ 30 , 31 , 32 ]. HER2 mutant patients with non-exon 20 mutations had an ORR comparable to exon 20 mutations [ 32 ].…”
Section: Treatment Of Her2-altered Nsclcmentioning
confidence: 99%
“…Studies have shown a 19–53% ORR and a median PFS of 5–6 months in pretreated HER2 mutant NSCLC, even in patients that received prior HER2 directed therapy [ 30 , 31 , 32 ]. HER2 mutant patients with non-exon 20 mutations had an ORR comparable to exon 20 mutations [ 32 ]. Pyrotinib has also been studied in in HER2 amplified NSCLC, demonstrating an ORR of 22.2%, and PFS of 6.3 months.…”
Section: Treatment Of Her2-altered Nsclcmentioning
confidence: 99%
See 1 more Smart Citation